Carbapenem-resistant Pseudomonas aeruginosa T3SS virulence genes and correlation between virulence and drug resistance and molecular epidemiology studies - Tang, Jianhua; Pu, Jiekun; Zhao, Linbo; Zhan, Xuli; Pang, Qianqian; Meng, Xiangyan; Feng, Rui; Fan, Haojun (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to investigate the relationship between the carriage and expression of virulence genes associated with the type III secretion system (T3SS) in carbapenem-resistant Pseudomonas aeruginosa (CRPA) and their impact on virulence, drug resistance, and molecular epidemiological patterns in clinical isolates.MethodsCRPA strains isolated from the First Hospital Affiliated to Hebei North College between April 2022 and February 2023 were analyzed. Antimicrobial susceptibility was tested using the microbroth dilution method. Second-generation high-throughput sequencing was employed to detect four virulence genes (exoU, exoY, exoS, and exoT) and β-lactamase genes in CRPA strains with T3SS. Multilocus Sequence Typing (MLST) was performed to determine the sequence types (ST) of the strains. The Galleria mellonella larvae assay was used to evaluate strain virulence and qPCR was used to measure the expression levels of virulence genes.ResultsResistance to imipenem was observed in 100% of the strains, whereas resistance to polymyxin B was the lowest at 6.7%. The highest detection rate of T3SS virulence genes was for exoT (100%), followed by exoS, exoY (88.9%), and exoU (11.1%). Twenty-two ST types were identified, with ST 244 being the most prevalent (31.1%). In the G. mellonella assay, five strains exhibited high virulence, 25 strains exhibited medium virulence, and 15 strains showed low virulence. Statistically significant differences in resistance rates to piperacillin/tazobactam, levofloxacin, and amikacin were observed among the CRPA strains with varying virulence levels (P < 0.05).ConclusionT3SS virulence genes and virulence levels in CRPA strains were correlated with antibiotic resistance. CRPA strains producing blaOXA-101 and blaPER-1 spread throughout the region.